Opting out of youth sports: how can we understand the social processes involved? - Persson, Marlene; Espedalen, Lars Erik; Stefansen, Kari; Strandbu, Åse (Sport, education and society, 2020)
Sports researchers often examine the subject of youth quitting sports through quantitative surveys using fixed-choice questionnaires. In this paper, we analyze 1,248 descriptions offered by youth in the survey Young in Oslo 2018 when asked to explain why they had left organized sports. We examine their reasons for opting out of sports and how different reasons may interact. Similar to studies with fixed-choice questions, we found both sports-internal and sports-external reasons for quitting. Our main finding concerns how sports-internal and sports-external processes appear together and reinforce the challenges some youth experience in their day-to-day lives in terms of their sports participation.